Senescence and the SASP: many therapeutic avenues - Birch, Jodie; Gil, Jesús (Genes & development, 2020)
Cellular senescence is a stress response that elicits a permanent cell cycle arrest and triggers profound phenotypic changes such as the production of a bioactive secretome, referred to as the senescence-associated secretory phenotype (SASP). Acute senescence induction protects against cancer and limits fibrosis, but lingering senescent cells drive age-related disorders. Thus, targeting senescent cells to delay aging and limit dysfunction, known as "senotherapy," is gaining momentum. While drugs that selectively kill senescent cells, termed "senolytics" are a major focus, SASP-centered approaches are emerging as alternatives to target senescence-associated diseases. Here, we summarize the regulation and functions of the SASP and highlight the therapeutic potential of SASP modulation as complimentary or an alternative to current senolytic approaches.